Chronic Sleep Restriction While Minimizing Circadian Disruption Does Not Adversely Affect Glucose Tolerance - Yuan, Robin K.; Zitting, Kirsi-Marja; Duffy, Jeanne F.; Vujovic, Nina; Wang, Wei; Quan, Stuart F.; Klerman, Elizabeth B.; Scheer, Frank A. J. L.; Buxton, Orfeu M.; Williams, Jonathan S.; Czeisler, Charles A. (Frontiers in Physiology, 2021)
Insufficient sleep, which has been shown to adversely affect metabolism, is generally associated with prolonged exposure to artificial light at night, a known circadian disruptor. There is growing evidence suggesting that circadian disruption adversely affects metabolism, yet few studies have attempted to evaluate the adverse metabolic effects of insufficient sleep while controlling for circadian disruption. We assessed postprandial glucose and insulin responses to a standard breakfast meal in healthy adults (n=9) who underwent three weeks of chronic sleep restriction (CSR) in a 37-day inpatient study while minimizing circadian disruption by maintaining the same duration of light exposure each study day. We compared these results to findings from an earlier inpatient study which used a forced desynchrony protocol to assess the influence of three weeks of CSR combined with recurrent circadian disruption (RCD) on glycemic control in healthy adults (n=21). CSR combined with RCD resulted in significantly elevated postprandial plasma glucose levels (p<0.0001), while CSR with minimized circadian disruption had no adverse glycemic effects after three weeks of exposure. These results suggest that one mechanism by which sleep restriction impacts metabolism may be via concurrent circadian disruption.